PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL COOPERATIVE TIPE COURSE REVIEW HORAY PADA PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Muhammad Siddiq; Reinita Reinita (Jurnal Bahana Manajemen Pendidikan, 2019)
This Study aims to determine the effect of Course Review Horay (CRH) modeling method on the student’s learning outcome in civic education. This research is a classroom action research using qualitative and quantitative approaches. In the implementation, this research consists of two cycles, namely cycle I two meetings and cycle II one meeting. Includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were 34 teachers and grade IV students.Student learning outcomes in research Cycle I 62.0 with good qualifications increased in cycle II to 86.64 with very good qualifications. Thus the Cooperative Learning model type Course Review Horay has been able to improve student learning outcomes in Integrated Thematic learning in class IV SDN 01 Benteng Pasar Atas Bukittinggi.The Key word: Course Review Horay (CRH) clasroom action research, Integrated Thematic learning